Anticandidal activity of phytochemicals extracted from medicinal plant eclipta prostrata (Funded Work) - RICHA RAGHUWANSHI; JAY KISHOR PRASAD; SANDEEP KUMAR GUPTA (International Journal of Pharma and Bio Sciences, 2018)
Eclipta prostrata is a widely used plant in traditional medicine for the treatment of several human diseases like hepatitis, asthma and skin infections. The antimicrobial spectrum of Eclipta prostrata was initially checked against fungus Aspergillus niger, Candida albicans and bacterial strains Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus. Phytochemicals extracted in organic solvents ethanol (70%), methanol (80%), chloroform (100%) and acetone (100%) were evaluated for their antimicrobial potential by agar well diffusion method. From the antibiogram analysis, it was observed that 70% Ethanolic leaves extract showed higher zone of inhibition against Candida albicans (22mm), Aspergillus niger (18.6mm) and bacterial strains Pseudomonas aeruginosa (20.6mm), Escherichia coli (19.9mm) and Staphylococcus aureus (21mm) compared to other organic solvents. Ethanolic leaves extract showing best results when added with Copper heavy metal augmented the anticandidal activity upto 2 fold and broad inhibition zones against Candida albicans (40mm) and Pseudomonas aeruginosa (25mm) were observed. It was thus concluded that Eclipta prostrata phytochemicals extracted in ethanol in combination with copper showed marked anticandidal activity.